Relationship Between Geopolitical Risk In Major Oil Producing Countries and Oil Price - Yuen, Tin Hei Alpha; Yuen, Wai Kee Thomas (International Journal of Energy Economics and Policy, 2022)
This study has applied Granger causality tests and dynamic ordinary least squares (DOLS) models to examine the relationship between geopolitical risk in major oil-producing countries and the crude oil price before and after the 2008 financial crisis. The granger causality tests show that the geopolitical risk of Saudi Arabia, Russia, the United States and China granger cause changes in crude oil prices. The DOLS models show that the series in the model are cointegrated. The coefficients for the geopolitical index of Canada, Russia and China are significant before the 2008 financial crisis sample period. However, the DOLS model shows that the coefficients for all geopolitical indexes are insignificant after the 2008 financial crisis sample period. The general public and investors generally precept major oil exporters like Russia and Saudi Arabia as the major players in the oil market. However, after the 2008 financial crisis, the discrepancy in the economic needs of the major oil-producing countries has reduced their ability to co-operate crude oil prices. This study also discovered that China plays a significant role in the oil market.